Pemberian Variasi Model Alat Pemungut Sampah Terhadap Frekuensi Memungut Sampah Murid TK Kudup Sari di Sidoluhur, Godean, Sleman, Tahun 2016 - Jati Khairudin; Adib Suyanto; sigid Sudaryanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Waste management can involve the entire community, including children. The involvement of very young children is a good first step for them to learn how to handle waste and to be respon-sible for caring the environment. The average age of Kudup Sari Kindergarten’s students, which is located in Sidoluhur, Godean, Sleman, is 6 years old. Children at this age are in the stage of imitating and receiving new knowledge easily. Therefore, it is expected that the children can easily apply the new received knowledge. This study was aimed to reveal the most preferred model of trash picking device among kindergarten children by conducting a quasi experiment which employed post-test only design. The population and sample of the study were all 41 stu-dents in the Class B of Kudup Sari Kindergarten. The observation was held in 10 times to ob-serve the number of children who pick the trash up that using the two picking models. Des-criptively, the difference of frequency average of trash picking is obvious, i.e. 4 times with the piercing model against 37 times with the clipping model. The result of independent t-test at 95 % level of confidence confirmed the difference since the obtained p-value that was smaller than 0,001, showing a significant disparity between the two averages. Therefore, this study shows that the clipping model is much more preferred by Kudup Sari Kindergarten students to pick trash than the piercing one.